VALIDITAS KONSTRAK INSTRUMEN ADAPTABILITAS KARIER BIDANG KELISTRIKAN - Nuha, Muhammad Yafie (Jurnal Edukasi Elektro, 2018)
AbstractThis research aims to get a proof of the validity career adapt-ability scale in the field of electrical construction. The samples in this research are electrical engineering education students, amounting to 146 students. The data analysis technique used in this research is second order confirmatory factor analysis (CFA). The compatibility of theoretical models with empirical data is determined with the coefficients of Chi-Square, p-value, CFI (Comparative Fit Index), and RMSEA (Root Mean Square Error of Approximation). The validity of each item in the career adapt-ability scale is determined with the value of factor loading, t value, and the significance level. Item is considered valid if the factor load is more than 0.3, the t-value is greater than 1.96, and the significance level is less than 5%. The validity of each factor of career adapt-ability is determined with CR (Construct Reliability) and average variance extracted (AVE). Based on the results of the analysis, it is found that the career adapt-ability instrument in the field of electricity consists of 20 items representing four factors, namely concern, control, curiosity, and confidence are categorized valid. Keywords: Construct Validity, Confirmatory Factor Analysis, and Career Adaptability. AbstrakPenelitian ini bertujuan untuk memperoleh bukti validitas instrumen pengukur konstrak adaptabilitas karier bidang kelistrikan. Sampel dalam penelitian adalah mahasiswa pendidikan teknik elektro yang berjumlah 146 mahasiswa. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis faktor konfirmatori orde kedua. Kesusuaian model teoritis dengan data empiris ditentukan dengan melihat koefisien Chi-Square, p-value, CFI (Comparatie Fit Index), dan RMSEA (Root Mean Square Error of Approxiamation). Validititas tiap item dalam konstrak adaptabilitas karier ditentukan dengan melihat nilai muatan faktor, nilai t, dan taraf signifikasinsi. Item dianggap valid jika muatan faktor lebih dari 0,3, nilai-t lebih besar daripada 1,96, dan taraf signifikansi kurang dari  5%. Validitas tiap faktor dari adaptabilitas karier ditentukan dengan melihat nilai CR (Construct Reliability) dan rerata varian terekstrak. Berdasarkan hasil analisis diperoleh bahwa instrumen adaptabilitas karier bidang kelistrikan terdiri atas 20 butir yang mewakili empat faktor, yaitu perhatian, kontrol, kengintahuan, dan kepercayaan  dapat dinyatakan valid.   Kata Kunci: Validitas Konstrak, Analisis Faktor Konfirmatori, dan Adaptabilitas Karier.